A project management improvement program according to ISO/IEC 29110 and PMBOK®. Issue 9 (5th August 2014) - Mesquida, Antoni‐Lluís; Mas, Antonia; Biró, M.; Messnarz, R.; Colomo‐Palacios, R.
ABSTRACT This paper describes the results obtained and the lessons learned from the implementation of the ISO/IEC 29110 standard in four small software development companies, clustered in a joint process improvement program. The main results of this initiative have been, on the one hand, the definition of a standardized set of processes and procedures and, on the other, the development of a Process Asset Library to support project management good practices within the participant organizations. The PMBOK® Guide was used to complement the ISO/IEC 29110‐5‐1‐2 standard, in order to provide detailed knowledge about project management inputs, outputs, and best techniques. Copyright © 2014 John Wiley & Sons, Ltd.